Tourniquet application in snake bite: are we aware? - Gargi, Gaveshna; Saini, Amit (International Journal of Research in Medical Sciences, 2020)
Background: To assess the use of tourniquets as mentioned in National Snake Bite Management Protocol among peripheral health care providers. Methods: This was a prospective cross-sectional study conducted in a tertiary care institute between June 2016 to June 2017. A total of 36 patients of snake bite referred from peripheral health facility were enrolled in the study and were evaluated for : date and time of bite, site of bite, weather snake was seen, type of envenomation, first aid given in Govt facility/alternative practitioner, tourniquet applied/not applied, anti snake venom given/not given as first aid and outcome. Results: The mean age of the study population was 39 years (17.38) range 18 years to 75 years. 18 patients were male and 18 were female. 30 (83.3%) patients had site of bite over the extremities’. The venom was hemotoxic in 12 (33.3%) patients and neurotoxic 21 (58.3%). 30 (83.3%) patients received first aid in the Government health facility manned by qualified in healthcare practitioner and 6 (16.7%) were treated by traditional healers. 29 (80.6%) patients had a tight tourniquet tied to the site of the bite when seen in emergency department of institute. None of the patients had their limbs splinted. 31 (86.1%) patients had received anti snake venom (ASV) at the peripheral health facility. The mortality rate was 5.6% with only 2 deaths. Conclusions: The majority of peripheral health care providers both qualified and unqualified use tourniquets in patients suffering with snake bite. The peripheral health care providers are not aware of importance of limb splinting and immobilisation. Though the rate of instilling ASV is good, the health care providers in the peripheral institutes should be made aware of recommendations of national snake bite management protocol with regard to use of tourniquets and limb splitting in snake bite patients.